Humanistic Approach: Implementation of Islamic Religious Education Learning to Increase Social Empathy Among students in junior high school - Siti aliyani; JM Ekafitrianda (At- Ta'lim : Jurnal Pendidikan, 2026)
This study examines the application of a humanistic approach in Islamic Religious Education (IRE) to improve students' social empathy at SMP Negeri Satu Atap 13 Sarolangun. This research is motivated by a decrease in students' social sensitivity and the persistence of teacher-centered learning practices that focus primarily on cognitive achievement. Qualitative descriptive methods are used to explore the learning process, teacher-student interaction, and the formation of empathy in the classroom. Data were collected through participatory observations, in-depth interviews, and documentation involving principals, IRE teachers, and eighth-graders. Data were analyzed using the Miles and Huberman models, including data subtraction, data display, and conclusion drawn. The findings show that humanistic approaches create a psychologically, dialogically, and student-centered learning environment. Teachers who demonstrate unconditional conformity, empathy, and positive attention are able to reduce students' anxiety and encourage open interaction. Social empathy develops through a gradual psychological process that consists of three phases: the creation of a sense of security, social interaction in cooperative learning, and the internalization of values through reflection. This study concludes that humanistic approaches are effective in fostering empathy and meaningful social relationships, even in schools with limited facilities.